Heterogeneity of the definition of elderly age in current orthopaedic research - Sabharwal,S; Wilson,H; Reilly,P; Gupte,CM (SpringerPlus, 2015)
Medical research often defines a person as elderly when they are 65 years of age or above, however defining elderly age by chronology alone has its limitations. Moreover, potential variability in definitions of elderly age can make interpretation of the collective body of evidence within a particular field of research confusing. Our research goals were to (1) evaluate published orthopaedic research and determine whether there is variability in proposed definitions of an elderly person, and (2) to determine whether variability exists within the important research sub-group of hip fractures. A defined search protocol was used within PubMed, EMBASE and the Cochrane Library that identified orthopaedic research articles published in 2012 that stated within their objective, intent to examine an intervention in an elderly population. 80 studies that included 271,470 patients were identified and subject to analysis. Four (5 %) studies failed to define their elderly population. The remaining 76 (95 %) studies all defined elderly age by chronology alone. Definitions of an elderly person ranged from 50 to 80 years and above. The most commonly used age to define an elderly person was 65, however this accounted for only 38 (47.5 %) of studies. Orthopedic research appears to favor defining elderly age by chronology alone, and there is considerable heterogeneity amongst these definitions. This may confuse interpretation of the evidence base in areas of orthopaedic research that focus on elderly patients. The findings of this study underline the importance of future research in orthopaedics adopting validated frailty index measures so that population descriptions in older patients are more uniform and clinically relevant.